Why Are Individuals Attracted to Organizations? - Ehrhart, Karen Holcombe; Ziegert, Jonathan C. (Journal of Management, 2005)
Applicant attraction is vital to the success of an organization. Despite its importance, however, research on it has tended to proceed in a relatively piecemeal way. Accordingly, the authors present a framework for attraction research through an examination of the underlying relevant theories. Specifically, they identify three overarching metatheories focusing on environment processing, interactionist processing, and self-processing that form the basis for their theoretical model. The authors conclude with an examination of future research directions.